The Danish savings surplus: Trends in firm and household savings - Henrik Yde Andersen; Lars Risbjerg; Morten Spange; Robert Wederkinck (Danmarks Nationalbank, 2024)
Over the past 30 years, Denmark has had a savings surplus in the sense that gross savings have exceeded gross investments. This is equivalent to a current account surplus, and it has been particularly evident since the global financial crisis in 2008. The savings surplus has to a large extent been accounted for by firms. While the level of investment of non-financial firms is comparable to other countries, their earnings and gross savings are high by international comparison. For households, healthy pension contributions have to some extent been offset by borrowing, but their financial wealth has been increasing due to valuation gains on financial assets.
Keywords: 330